Gold nanoparticle/polymer nanocomposites dispersion of nanoparticles as a function of capping agent molecular weight and grafting density - Corbierre, Muriel K (Langmuir : the ACS journal of surfaces and colloids, 2005)
The dispersion of polymer-covered gold nanoparticles in high molecular weight (MW) polymer matrixes is reported. Complete particle dispersion was achieved for PS125-Au in the polystyrene (PS) matrixes studied (up to and including Mn = 80 000 g/mol). PS19-Au, on the other hand, exhibits complete dispersion in a low MW PS matrix (Mn = 2000 g/mol) but only partial dispersion in higher MW matrixes (up to 80 000 g/mol). Similarly, PEO45-Au is fully dispersed in a low MW poly(ethylene oxide) (PEO) matrix (Mn = 1000 g/mol) but only partially in a higher MW PEO matrix (Mn = 15 000 g/mol). Wetting of the polymer-Au brushes by the polymer matrix is associated with dispersibility. Theory predicts that, for dense polymer brushes, wetting is achieved when the MW of the polymer brush equals (and is greater than) that of the polymer matrix. The observed partial dispersion of the PS19-Au and PEO45-Au nanoparticles in matrixes whose MW is greater than the brush MW is attributable to the existence of a high volume fraction of voids within the brush. These voids arise from the unique geometry of the nanoparticle surface arising from the juxtaposed facets of the gold nanoparticle. PS125-Au brushes are wetted by PS matrixes whose degree of polymerization is larger than 125, probably because of their lower grafting density on the gold core or the high fraction of void volumes caused by the facets on the gold cores. Dispersion thus occurs when the matrix MW is greater than that of the brush